OPTIMALISASI PENERAPAN HUKUM PIDANA PENCUCIAN UANG DALAM MENJERAT PELAKU TINDAK PIDANA PERPAJAKAN (Studi kasus putusan pengadilan Rinaldus Andry Suseno) - Immanuel Titus; Rizky Karo Karo (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
This research is based on the complexity of white-collar crimes involving illegal taxation and money laundering as an attempt to disguise the proceeds of crime. Tax crimes are often only subject to administrative sanctions, making the approach through Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering a more effective legal strategy. This research aims to analyze the application of money laundering articles to perpetrators of tax crimes and assess the effectiveness of this approach in the Indonesian legal system. The research method used is a case study with a normative-juridical approach, using secondary data in the form of court decisions and related laws and regulations. The results show that in the Rinaldus case, the court successfully proved the link between tax crimes as a predicate crime and money laundering as a follow-up. This strategy allows law enforcement officials to ensnare the perpetrator with the threat of harsher penalties and confiscate assets derived from the crime. The conclusion of this research is that the application of money laundering criminal law has proven effective in strengthening law enforcement against tax crimes and increasing the deterrent effect, while also demonstrating progressive developments in the Indonesian economic criminal law system.